CHECKLIST OF THE LARGE CENTIPEDES (CHILOPODA: SCOLOPENDROMORPHA) FROM LO GO - XA MAT NATIONAL PARK, TAY NINH PROVINCE, VIETNAM - Le, Xuan Son; Do, Tat Thinh; Nguyen, Huu Thuc; Nguyen, Duc Hung; Tran, Thi Thanh Binh; Nguyen, Duc Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A study on the large centipede fauna (Chilopoda: Scolopendromorpha) was conducted in Lo Go - Xa Mat National Park (Tay Ninh Province, southern Vietnam) through two field surveys in March and July 2024. The primary aim of the study was to provide a species checklist for the national park and to update taxonomic and distributional data of scolopendromorph centipedes in a tropical region that remains poorly explored. Specimens were collected using standard soil fauna sampling techniques, including quadrat digging, soil sieving, pitfall trapping, and random sampling along forest transects. All specimens were preserved in ethanol and examined morphologically under stereomicroscopes for taxonomic identification. A total of eleven species and subspecies belonging to five genera and three families within the order Scolopendromorpha were identified, including: Alluropus calcaratus, Cryptops (Cryptops) tahitianus, Cryptops (Paracryptops) indicus, Otostigmus aculeatus, Otostigmus multidens, Otostigmus politus, Otostigmus scaber, Scolopendra dehaani, Scolopendra gracillima sternostriata, Scolopendra morsitans, and Scolopendra subspinipes. Among these, nine species and subspecies represent new records for the area. Although Scolopendra morsitans had been previously reported from the park, it was not encountered in the present study. This study provides an updated checklist of scolopendromorph species in Lò Gò - Xa Mát National Park, together with details of the specimen collection sites and species distributions in Vietnam and globally. The results highlight the high species richness and ecological significance of the park for invertebrate conservation. Moreover, the findings contribute to the national taxonomic database and serve as a scientific basis for biodiversity monitoring, conservation planning, and ecological management in Vietnam.